Implementasi Problem Based Learning Berbantuan Teks Cerita untuk Meningkatkan Keterampilan Berpikir Kritis Materi Keragaman Sosial Budaya Siswa Kelas VII SMPN 40 Surabaya - Nur Alfiyani; Rizqa Nadhifah; Berlinda Pujianti; Neka Tankira; Erlina Firdaus; Ita Mardiani Zain (PT. Penerbit Tiga Mutiara, 2026)
Critical thinking skills are a 21st-century competency that needs to be developed through contextual and problem-solving-based Social Studies learning. However, Social and Cultural Diversity learning in junior high schools still faces challenges because students tend to memorize concepts, have limited ability to analyze social issues, and experience difficulties in constructing evidence-based arguments. This study aims to analyze the implementation of Problem Based Learning assisted by story texts to improve the critical thinking skills of seventh-grade students at SMPN 40 Surabaya. The research employed Collaborative Classroom Action Research using qualitative and quantitative approaches through two action cycles. Data were collected through tests, observations, interviews, and documentation. The results showed an increase in the average score from 57.80 in Cycle I to 72.33 in Cycle II. The integration of Problem Based Learning and story texts represents the novelty of this study by presenting authentic socio-cultural conflicts to strengthen students’ analysis, evaluation, and argumentation skills. These findings provide theoretical contributions to constructivist learning and practical implications for teachers in designing active, meaningful, and critical Social Studies learning.